О геологическом возрасте ископаемых костей млекопитающих из района Каневской ГЭС - Свистун, В.И.; Ломаев, А.А. (Вестник зоологии, 1967)
In 1965-1966 the paleontologic expedition of the Institute of Zoology, Academy of Sciences of the Ukrainian SSR carried out the investigations in the pits of building and sluice of the Kanev hydro-electric power station. Here in the alluvial deposits of the Dnieper a considerable osteological material was collected. Bone remains were deposited in the whole thickness of alluvial sands washed away by hydromonitors. But in some cases an accumulation of the bones was found on the basal level of alluvium, deposited in black-green boulder loarns or on the sands and schistous sandy loarns of lake-alluvial origin. Bones from these places were analysed for determination of geological age by col-lagenic method. On the basis of analysis it is determined that the majority of bones from the basal level and from the thickness of alluvium refers to the Middle Holocene (the Late Wurm).